Adoption of 37mm Maxim Automatic Guns by Russian Navy in Late 19th to Early 20th Century - A. V. Kislitsyn (Научный диалог, 2025)
This study investigates the adoption of Maxim automatic guns by the Russian Navy during the late 19th and early 20th centuries. It explores the close relationship between this topic and the development of naval artillery in Russia, as well as the dynamics of the domestic military-industrial complex and the functioning of the Ministry of the Navy of the Russian Empire during the period in question. The relevance of this research is underscored by the limited scholarship on the subject and its significance for analyzing historical experiences in weapon development. An analysis of archival sources is conducted, with many documents being introduced into scholarly discourse for the first time. The author concludes that the Russian military industry of that era was ill-prepared for the production of automatic guns. It is reported that the Ministry of the Navy deemed it unnecessary to allocate substantial financial resources for organizing their production through foreign companies. The study reveals that the ministry opted for a compromise solution, acquiring a limited number of new weapons with the intention of subsequently establishing production capabilities within domestic enterprises. Ultimately, it is established that Maxim automatic guns were never adopted by the Russian army and navy, both of which were in dire need of such weaponry during World War I.